Geochemistry and the Biosphere Essays. - Vernadsky, Vladimir I. (Synergetic Press, 2018)
This new volume introduces the Russian-Ukrainian scientist Vladimir I. Vernadsky, largely known in Eastern Europe through his groundbreaking 1926 monograph, The Biosphere.